High cycle fatigue behavior of 316L stainless steel manufactured via directed energy deposition with varying laser energy - Boey, Kai Jun (Nanyang Technological University, 2021)
One major concern associated with directed energy deposition (DED) process is the mechanical response of DED parts when subjected to cyclic loading with the appearance of defects like porosity. In this project, 316L stainless steel (SS) blocks was manufactured through DED using varying laser energies. Microstructures of as-built 316L SS blocks are characterization with emphasis on porosity by employing optical microscopy (OM) and scanning electron microscopy (SEM). Results have shown that volume fraction of porosity reduces monotonously with increasing laser energy, accompanied by a transition in porosity category from lack of fusion defects to gas-entrapped porosity. Rotating bending fatigue (RBF) tests were performed on all these blocks to explore high cycle fatigue (HCF) behaviors of samples containing different microstructures. Results show that fatigue strength also increases monotonously with increasing laser energy and a key reason can be that less and smaller porosity is presented in samples manufactured using high laser energy. This project shows that it is imperative to mitigate/eliminate porosity in DED parts subjected to cyclic loading via processing parameter optimization.